Che-1/AATF: A Critical Cofactor for Both Wild-Type- and Mutant-p53 Proteins - Bruno, Tiziana; Iezzi, Simona; Fanciulli, Maurizio (Frontiers in Oncology, 2016)
The p53 protein is a key player in a wide range of protein networks that allow the state of "good health" of the cell. Not surprisingly, mutations of the p53 gene are one of the most common alterations associated to cancer cells. Mutated forms of p53 (mtp53) not only lose the ability to protect the integrity of the genetic heritage of the cell, but acquire pro-oncogenic functions, behaving like dangerous accelerators of transformation and tumor progression. In recent years, many studies focused on investigating possible strategies aiming to counteract this mutant p53 “gain of function” but the results have not always been satisfactory. Che-1/AATF is a nuclear protein that binds to RNA polymerase II and plays a role in multiple fundamental processes, including control of transcription, cell cycle regulation, DNA damage response and apoptosis. Several studies showed Che-1/AATF as an important endogenous regulator of p53 expression and activity in a variety of biological processes. Notably, this same regulation was more recently observed also on mtp53. The depletion of Che-1/AATF strongly reduces the expression of mutant p53 in several tumors in vitro and in vivo, making the cells an easier target for chemotherapy treatments. In this mini review, we report an overview of Che-1/AATF functions and discuss a possible role of Che-1/AATF in cancer therapy, with particular regard to its action on p53/mtp53.